Characterization of ovarian cancer-derived extracellular vesicles by surface-enhanced Raman spectroscopy. Issue 23 (29th October 2021) - Ćulum, Nina M.; Cooper, Tyler T.; Lajoie, Gilles A.; Dayarathna, Thamara; Pasternak, Stephen H.; Liu, Jiahui; Fu, Yangxin; Postovit, Lynne-Marie; Lagugné-Labarthet, François
Abstract : EVs derived from normal ovarian (hIOSE) and ovarian cancer (OVCAR3, OV-90, EOC6, EOC18) cells were analysed by SERS. The SERS spectra of normal and cancer EVs were differentiated by PCA and machine learning, through which we achieved >99% accuracy. Abstract : Ovarian cancer is the most lethal gynecological malignancy, owing to the fact that most cases are diagnosed at a late stage. To improve prognosis and reduce mortality, we must develop methods for the early diagnosis of ovarian cancer. A step towards early and non-invasive cancer diagnosis is through the utilization of extracellular vesicles (EVs), which are nanoscale, membrane-bound vesicles that contain proteins and genetic material reflective of their parent cell. Thus, EVs secreted by cancer cells can be thought of as cancer biomarkers. In this paper, we present gold nanohole arrays for the capture of ovarian cancer (OvCa)-derived EVs and their characterization by surface-enhanced Raman spectroscopy (SERS). For the first time, we have characterized EVs isolated from two established OvCa cell lines (OV-90, OVCAR3), two primary OvCa cell lines (EOC6, EOC18), and one human immortalized ovarian surface epithelial cell line (hIOSE) by SERS. We subsequently determined their main compositional differences by principal component analysis and were able to discriminate the groups by a logistic regression-based machine learning method with ∼99% accuracy, sensitivity, and specificity. The results presented here are a great step towards quick, facile, and non-invasive cancer diagnosis.